AFRICAN VOICES AND DEMANDS ON THE UNITED NATIONS GENERAL ASSEMBLY @80 - Theresa Egwure Chima (PT. Antis International Publisher, 2026)
Objective: The article evaluates the voices and demands of African leaders on the United Nations General Assembly @80. The paper focuses on African leader’s unified, assertive demands for a fundamental restructuring of the global order. Method: The study selected the demands of some African leaders through the voices of four African Presidents: Algeria- President Abdelmajid Tebboune, Kenya- President William Ruto, Nigeria- President Bola Ahmed Adekunle Tinubu, highly represented by the Vice President Kashim Shettima Mustapha and Ghana- President John Dramani Mahama. Results: The paper concludes that African leaders made key demands which centered on ending historical marginalization, which includes: Reform and fair representations of African States in the UN Security Council, aid dependency to self-reliance and development, fair trade and resource value addition, peace, security and human rights, climate change and sustainable development, finally, data sovereignty, migration governance and African led solution. Novelty: The paper recommends equitable representation in global governance by fostering fair economic partnership and development.